A Neuroeconomic Theory of Mental Time Travel - Brocas, Isabelle; Carrillo, Juan D. (Frontiers in Neuroscience, 2018)
We propose a theoretical model that places attention at the center of mental time travel ability. This theory predicts that attention promotes a memory-based process that encodes memories of unexpected events, facilitates accurate recollection of information of such events during mental time travel, and optimizes subsequent decision-making. This process coexists with a habitual process that governs all other events and treats them equally. Our theory demonstrates that the memory-based process is useful when the environment features novel experiences that are likely to be relevant in future decision-making, hence worth remembering accurately. By contrast, the habitual process is optimal in environments that either do not change significantly, or have a small chance of being repeated in the future. This may explain why the ability to mentally travel in time has developed differently in humans than in other species. Implications are discussed in the context of decision-making.